Integrative analyses of biomarkers and pathways for diabetic nephropathy - Li, Bo; Zhao, Xu; Xie, Wanrun; Hong, Zhenzhen; Zhang, Yi (Frontiers in Genetics, 2023)
Background Diabetic nephropathy (DN) is a common complication of diabetes mellitus, which is one of the leading causes of end-stage renal disease. There is no doubt that DN is a chronic disease that imposes substantial health and economic burdens on the world's population. By now, some impressive progress has been made in the study of pathogenesis. However, the molecular mechanisms underlying these effects remain unknown. Methods Analyses of differentially expressed genes (DEGs), enrichment of gene ontology (GO), the Kyoto Encyclopedia of Genes and Genomes (KEGG), and gene set enrichment analysis (GSEA) were performed. String databases were used to construct protein-protein interaction (PPI) networks. Cytoscape software was used to identify hub genes and identify common hub genes by taking intersection sets. The diagnostic value of common hub genes was then predicted in the GSE30529 and GSE30528 datasets. Further analysis was carried out on the modules to identify transcription factors and miRNA networks. As well, the comparative toxicological genomics database (CTD) was used to evaluate the interaction between potential key genes and DN. Results We identified 86 up-regulated genes and 34 down-regulated genes (a total of 120 DEGs). The GO analysis of common DEGs was significantly enriched in humoral immune response, protein processing, protein activation cascade, complement activation, antigen binding, and so on. The KEGG analysis was significantly enriched in complement and coagulation cascades, the phagosome, the Rap1 signaling pathway, the PI3K-Akt signaling pathway, and infection. GSEA enrichment analysis showed that DEGs were mainly enriched in TYROBP causal network, Interferon γand α signaling pathways, ECM receptor interaction, integrin1 pathway, and so on. Meanwhile, co-expressed mRNAs and miRNAs were selected to construct mRNA-miRNA interaction networks. eight hub genes (TYROBP, ITGB2, CD53, IL10RA, LAPTM5, CD48, C1QA, and IRF8) were finally identified as having diagnostic value. Conclusions The target genes TYROBP, ITGB2, CD53, IL10RA, LAPTM5, CD48, C1QA, and IRF8 are promising new targets for diabetic nephropathy. The transcription factors HIF1A, KLF5, RUNX1, SP1, SPI1, STAT1, MBD1, and WT1 may be involved in the regulatory mechanisms of diabetic nephropathy development.